Bounded Rationality and Robust Mechanism Design: An Axiomatic Approach - Zhang, Luyao; Levin, Dan (American Economic Review, 2017)
We propose an axiomatic approach to study the superior performance of mechanisms with obviously dominant strategies to those with only dominant strategies. Guided by the psychological inability to reason state-by-state, we develop Obvious Preference as a weakening of Subjective Expected Utility Theory. We show that a strategy is an obviously dominant if and only if any Obvious Preference prefer it to any deviating strategy at any reachable information set. Applying the concept of Nash Equilibrium to Obvious Preference, we propose Obvious Nash Equilibrium to identify a set of mechanisms that are more robust than mechanisms with only Nash Equilibria.